EFEKTIVITAS DISPENSASI PERKAWINAN DI BAWAH UMUR UNTUK KEHARMONISAN RUMAH TANGGA DI WILAYAH KANTOR URUSAN AGAMA (KUA) KECAMATAN NOGOSARI KABUPATEN BOYOLALI - Sanduri, S; Wibowo, Muhammad Kurniawan Budi; Baehaqi, B (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
Marriage dispensation is an effort for those who want to get married but have not met the age limit set by the government. Underage marriages cause various kinds of problems, according to the Marriage Law No. . The focus of the issues discussed are: 1) How is the marriage dispensation process. 2) How is the effectiveness of underage marriage dispensation for household harmony in Nogosari District? This study aims to determine the effectiveness of dispensing underage marriages for household harmony, what are the strategies used by early marriage couples in creating a harmonious family. This research is called field research, in this study taking primary data from the field which was studied intensively accompanied by an analysis of all data or information that has been found, the results of the research show that the effectiveness of underage marriage dispensation for household harmony is lacking effective because of the 30 informants interviewed by the researchers 80% of them experienced a lack of harmony in the household, this occurred due to several factors including: 1) Psychologically and socio-economically the marriage partners were immature. 2) They are classified as still unstable. 3) Don't have much knowledge about how to care for children, so they can't apply proper parenting patterns.